Global Fund-supported programmes’ contribution to international targets and the Millennium Development Goals: an initial analysis - Ryuichi Komatsu; Daniel Low-Beer; Bernhard Schwartländer (Bulletin of the World Health Organization, 2007)
ABSTRACT OBJECTIVE: The Global Fund to Fight AIDS, Tuberculosis and Malaria is one of the largest funders to fight these diseases. This paper discusses the programmatic contribution of Global Fund-supported programmes towards achieving international targets and Millennium Development Goals, using data from Global Fund grants. METHODOLOGY: Results until June 2006 of 333 grants supported by the Global Fund in 127 countries were aggregated and compared against international targets for HIV/AIDS, tuberculosis and malaria. Progress reports to the Global Fund secretariat were used as a basis to calculate results. Service delivery indicators for antiretrovirals (ARV) for HIV/AIDS, case detection under the DOTS strategy for tuberculosis (DOTS) and insecticide-treated nets (ITNs) for malaria prevention were selected to estimate programmatic contributions to international targets for the three diseases. Targets of Global Fund-supported programmes were projected based on proposals for Rounds 1 to 4 and compared to international targets for 2009. FINDINGS: Results for Global Fund-supported programmes total 544 000 people on ARV, 1.4 million on DOTS and 11.3 million for ITNs by June 2006. Global Fund-supported programmes contributed 18% of international ARV targets, 29% of DOTS targets and 9% of ITNs in sub-Saharan Africa by mid-2006. Existing Global Fund-supported programmes have agreed targets that are projected to account for 19% of the international target for ARV delivery expected for 2009, 28% of the international target for DOTS and 84% of ITN targets in sub-Saharan Africa. CONCLUSION: Global Fund-supported programmes have already contributed substantially to international targets by mid-2006, but there is a still significant gap. Considerably greater financial support is needed, particularly for HIV, in order to achieve international targets for 2009.